Ultrasonic assisted reflow soldering of lead free solder joint / Tan Ai Ting - Tan, Ai Ting (2017)
The present thesis focused on the development of ultrasonic assisted reflow soldering technique to improve the reliability of lead free solder joint in the electronic packaging application by integrating ultrasonic vibration (USV) into the reflow stage of a reflow soldering process. In the preliminary phase, Cu/Sn-Ag-Cu/Cu lead free solder joints were successfully fabricated by using 20 kHz USV with 169 W (high-power-low-frequency USV) and 55 kHz USV with 10 W (low-power-high-frequency USV). The material characterization tests revealed that the solder matrix microstructure was refined and the formation of interfacial intermetallic compound (IMC) was reduced after treated with both types of USV. This is attributed to the USV induced nucleation of β-Sn and eutectic phases as well as the homogeneity effect on the mass and heat transfer in the fully liquefied SAC solder. Additionally, USV induced degassing mechanism has taken effect on the size reduction of macrovoids in the solder joint which enhanced the shear strength of the ultrasonic-treated solder joints in return. The study also expressed the variation of USV time and its influence on the microstructural and mechanical properties of the solder joints. Coarsening of solder matrix was observed at prolonged USV time when using low-power-high-frequency USV. This may be associated with the prolonged of acoustic streaming induced by USV in the molten SAC, which allowed the nucleated β-Sn, Cu6Sn5 and Ag3Sn crystals to grow larger with time. However, the solder joints with coarsened solder matrix microstructure exhibited higher shear strength compared to those with refined microstructure. Therefore, in the subsequent study, the effect of ultrasonic power on the solder joint properties was investigated by using low-power-high-frequency USV. The results revealed that higher ultrasonic power would induce greater superheating effect and promoted the formation of eutectic phase in the solder joints. Furthermore, the shear stress-strain curve acknowledged that the strength enhancement on the solder joint with coarsened solder matrix microstructure was contributed by the strain hardening mechanism of the coarser β-Sn phase. Overall, the present studies progressively presented the caliber of the proposed ultrasonic assisted reflow soldering technique in producing reliable lead free solder joint with homogeneous solder matrix microstructure, thinner IMC and improved shear strength. These evidences demonstrate the potential use of ultrasonic assisted reflow soldering as a beneficial approach for the fabrication of lead free solder joints.